2023
DOI: 10.3390/cancers15071931
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Mediastinal Bulky Lymphomas with FDG-PET-Based Radiomics and Machine Learning Techniques

Abstract: Background: This study tested the diagnostic value of 18F-FDG PET/CT (FDG-PET) volumetric and texture parameters in the histological differentiation of mediastinal bulky disease due to classical Hodgkin lymphoma (cHL), primary mediastinal B-cell lymphoma (PMBCL) and grey zone lymphoma (GZL), using machine learning techniques. Methods: We reviewed 80 cHL, 29 PMBCL and 8 GZL adult patients with mediastinal bulky disease and histopathological diagnoses who underwent FDG-PET pre-treatment. Volumetric and radiomic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Recently, 18 F-FDG PET/CT radiomics-based ML analysis has been applied to overcome these issues [ 75 ]. Previous studies have revealed that 18 F-FDG PET/CT radiomics-based ML analysis is useful in not only classifying tumors based on histological subtypes but also differentiating malignant lymphoma from other diseases [ 76 80 ].…”
Section: Clinical Application Of 18 F-fdg Pet/ct R...mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, 18 F-FDG PET/CT radiomics-based ML analysis has been applied to overcome these issues [ 75 ]. Previous studies have revealed that 18 F-FDG PET/CT radiomics-based ML analysis is useful in not only classifying tumors based on histological subtypes but also differentiating malignant lymphoma from other diseases [ 76 80 ].…”
Section: Clinical Application Of 18 F-fdg Pet/ct R...mentioning
confidence: 99%
“…Abenavoli et al [ 76 ] showed that the ML model with the RF algorithm using PET-radiomics had a better performance in differentiating diffuse large B-cell lymphoma (DLBCL) from Hodgkin’s lymphoma (HD) based on SUVmax (AUC: 0.87 vs. 0.78). de Jesus et al [ 77 ] reported that the ML model with the gradient boosting algorithm using PET/CT radiomics had a significantly higher AUC in distinguishing DLBCL and follicular lymphoma according to SUVmax (AUC:0.86 vs. 0.79, p < 0.01).…”
Section: Clinical Application Of 18 F-fdg Pet/ct R...mentioning
confidence: 99%
“…Such intratumor heterogeneity correlates not only with molecular subtypes, but also with biological factors that can be associated with different tumor aggressiveness and prognosis. [16][17][18] Recent research demonstrated the promising role of textural analysis from both CECT and PET imaging in predicting prognosis in HL patients. [19][20][21][22] However, no radiomic studies focused specifically on HL patients affected by bulky lymphomas.…”
Section: Introductionmentioning
confidence: 99%